Psychological Distress in a Sample of Inpatients With Mixed Cancer—A Cross-Sectional Study of Routine Clinical Data - Peters, Luisa; Brederecke, Jan; Franzke, Anke; de Zwaan, Martina; Zimmermann, Tanja (Frontiers in Psychology, 2020)
Background: The diagnosis and treatment of cancer are associated with psychosocial psychological distress that often leads to a significant reduction in emotional and physical well-being and quality of life. Early detection of psychological distress is therefore important. This study aims to assess the psychological distress of inpatient cancer patients using routine clinical data. Furthermore, variables and problems most strongly associated with psychologicalsocial distress should be identified. Material and Methods: N = 1869 inpatients were investigated (mean age = 60.89 years; 35.94% female) using the NCCN Distress Thermometer (DT) and problem checklist in order to assess distress as well as multiple possible problem areas. Visceral oncological cancer (31.6%) was the most common tumor diagnosis followed by skin cancer (26.2%) and urological cancer (21.7%). Results: 65.9% of the sample experienced high levels of distress (DT ≥ 5). Female gender, advanced stage 4s of disease and visceral and head & neck cancer emerged as risk factors for high distress. A younger age (< 65 years) was significantly correlated with higher distress. The most frequently self-reported problems were fears (50.1%), worry (49.9%) and fatigue (49.1%). Patients with all three of these problems had a 24 times higher risk (OR = 23.9) for high levels of distress than patients without these problems. Women reported significantly more practical, emotional and physical problems than men. Younger (<50 years) and middle-aged patients (50-64 years) reported increased levels of practical, family and emotional problems compared to older patients (≥ 65 years). Discussion: Almost two thirds of the sample reported high levels of distress. The most frequently reported problem areas were emotional and physical problems. These results can help to identify patients with high risk for psychologicalsocial distress and therefore be used to optimize psychosocial and psycho-oncological care for patients with cancer.